Intracranial hemangiopericytoma: Case study with cytogenetics and genome wide SNP-A analysis - Holland, Heidrun; Livrea, Michela; Ahnert, Peter; Koschny, Ronald; Kirsten, Holger; Meixensberger, Jürgen; Bauer, Manfred; Schober, Ralf; Fritzsch, Dominik; Krupp, Wolfgang (Pathology, research and practice, 2011)
The tumor entity of hemangiopericytoma is not universally recognized as a nosological entity by pathologists, and there is a trend toward reassigning it to other categories gradually. However, hemangiopericytomas occurring in the nervous system are included in the new WHO classification of brain tumors, and are distinguished from both meningioma and fibrous tumors. Since there are few genetic studies, we performed a comprehensive cytogenetic analysis of an infratentorial hemangiopericytoma in a 55-year-old female. It was originally classified as a grade II tumor but recurred as a grade III tumor with a proliferation index of 20%. Using trypsin-Giemsa staining (GTG-banding) and multicolor fluorescence in situ hybridization (M-FISH), we could confirm the loss of chromosomal material 10q, which has been previously described in hemangiopericytoma, and we identified de novo chromosomal aberrations on chromosome 8. Applying genome-wide high-density single nucleotide polymorphism array (SNP-A) analysis, we detected segments with loss or gain, as well as clonal deletions or regions suggestive of segmental uniparental disomy. These findings, together with the results of conventional histological and immunohistochemical characterization, provide additional evidence for the nosological separation of hemangiopericytoma in the central nervous system as a biologically different entity.
Gesehen am 29.06.2022